IMPLEMENTASI PERLINDUNGAN OJK TERHADAP PEMEGANG SAHAM PERUSAHAAN EMITEN AKIBAT DELISTING OLEH BURSA EFEK INDONESIA - Fani Ramadani; Hj. Zulhelmi (Adisam Publisher, 2024)
This research discusses the protection of the Financial Services Authority against shareholders of listed companies due to delisting by the Indonesia Stock Exchange where when a listed company or issuer experiences conditions that significantly affect the price of a share, the issuer will be given sanctions in the form of a suspension so that the issuer can improve company performance, but if the suspension is more than 24 months then the issuer will be delisted by the Indonesia Stock Exchange. As a legal consequence of delisting, investors are also harmed because the shares owned will lose value. Meanwhile, from a sharia perspective, the protection of shareholders due to delisting must be in accordance with maqāsid ash-shari'ah (sharia objectives). The principles of benefit in Islamic law must also be fulfilled, including the benefit of many people, realizing social justice, not burdensome and a little burden. Therefore, it is necessary to protect investors by authorized institutions, namely the Financial Services Authority, which is clear and can facilitate all related parties so that no party gets the biggest loss. The purpose of this study is to examine how the implementation of OJK protection against investors as the injured party due to delisting of the issuer's shares. The type of research used is qualitative research with a descriptive approach. The type of data used is secondary data. The data collection techniques used are through documentation and analysis of delisting cases. Documentation data is obtained through the Indonesia Stock Exchange while regulations as investor protection are obtained from applicable laws such as the Law, POJK and provisions on the Indonesia Stock Exchange.